Navigating the AI chip divide: Malaysia’s strategic dilemma in a fractured tech order - Jalal Nori, Abdulwahed (China Daily, 2025)
The United States’ recent move to restrict the export of advanced AI chips to Malaysia and Thailand is far more than a targeted regulatory action. It is a calculated gesture in a broader geopolitical strategy that seeks to redraw the global technological landscape. The draft rule, proposed by the US Commerce Department, must be read not merely as a measure against illicit semiconductor smuggling, but as part of a wider effort to construct a new architecture of digital control—where supply chains are weaponized, technological ecosystems are bifurcated, and innovation itself is deployed as a tool of geopolitical leverage.